Mobile Technology, Cancer Prevention, and Health Status among Diverse, Low-Income Adults - Purnell, Jason Q. (2013)
PURPOSE: Characterize mobile technology ownership, use, and relationship to self-reported cancer prevention behaviors and health status in a diverse, low-income sample of callers to 2-1-1. DESIGN: Secondary analyses of cross-sectional survey data from a larger trial collected from June 2010 to December 2012. SETTING: United Way Missouri 2-1-1 serves 99 of 114 counties and received 166,000 calls in 2011. SUBJECTS: The respondents (baseline n = 1,898; 4-month n = 1,242) were predominantly female, non-Hispanic Black, under 50, with ≤ high school education and annual income < $20,000. MEASURES: Cell phone ownership and use and its relationship to cancer prevention services and health status were assessed via telephone-based survey using items adapted from previous research and the BRFSS. Smartphone ownership and use were also assessed. ANALYSIS: Descriptive statistics and bivariate and multivariate associations between cell phone ownership and prevention and health status are reported. RESULTS: Three-fourths (74%) of study participants owned a cell phone and 19% owned a smartphone. Text messaging was the most popular use. Ownership was significantly associated with good to excellent health status and presence of smoke-free home policies in multivariate models. CONCLUSION: Cell phone ownership is growing and has potential to deliver health information to low-income populations. With 16 million calls annually, the national 2-1-1 system may be a promising model and platform.